2006
DOI: 10.1159/000093867
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Potential Interactive Genetic Factors in Huntington’s Disease

Abstract: Aim: To assess the role of genetic factors, other than the CAG repeat length, on the development of Huntington’s disease (HD) in an isolated Caucasian population in the south-west of Western Australia. Methods: 114 patients with symptomatic HD according to the Unified HD Rating Scale research criteria were examined along with 51 control patients. The length of the CAG repeat sequence in the IT15 gene and the adjacent CCG and Δ2642 polymorphisms were determined by polymerase chain reaction along with common gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
(33 reference statements)
0
11
0
1
Order By: Relevance
“…Specifically, APOE had been linked to Parkinson disease (PD) (149,150), chronic traumatic encephalopathy (151), Huntington disease (152,153), frontotemporal dementia (FTD) (154), and certain subsets of amyotrophic lateral sclerosis (155)(156)(157), though the latter findings conflicted with some other studies (158)(159)(160). Here, we discuss the current state of knowledge on the specific interaction between APOE and the aggregation-prone proteins associated with some of these diseases.…”
Section: Apoe and Other Amyloidogenic Proteinsmentioning
confidence: 95%
“…Specifically, APOE had been linked to Parkinson disease (PD) (149,150), chronic traumatic encephalopathy (151), Huntington disease (152,153), frontotemporal dementia (FTD) (154), and certain subsets of amyotrophic lateral sclerosis (155)(156)(157), though the latter findings conflicted with some other studies (158)(159)(160). Here, we discuss the current state of knowledge on the specific interaction between APOE and the aggregation-prone proteins associated with some of these diseases.…”
Section: Apoe and Other Amyloidogenic Proteinsmentioning
confidence: 95%
“…15,24 The potential correlation between the polymorphic CCG region and the age of onset of the disease is controversial. According to Panegyres et al, 25 who studied an Australian population, the CCG region does not correlate with the age of onset of HD, the neurological symptoms or the number of CAG repeats. On the other hand, Chattopadhyay et al 26 found that, in an Indian population, variation in the length of the CCG region was responsible for 3.1% of variation in the age of onset of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…It is well known that the HD expansion is overrepresented on a subset of the haplotypes associated with non-disease-associated alleles. Notably, a potential methylationmodifying polymorphism exists in the form of the polymorphic CCG repeat, which lies immediately downstream of the CAG repeat 21 and tags many of the most common HTT haplotypes. We evaluated five multivariate linear regression models to examine if the association between HTT cg22982173 and CAG length could possibly arise as an artifact of linkage disequilibrium between the CAG repeat and some other methylation-modifying variants at the HTT locus ("Methods").…”
Section: Resultsmentioning
confidence: 99%